The human small glutamine-rich TPR-containing protein is required for progress through cell division - Winnefeld, Marc; Rommelaere, Jean; Cziepluch, Celina (Experimental cell research, 2003)
Eukaryotic organisms from yeast to human harbor genes encoding the small glutamine-rich tetratricopeptide repeat-containing (SGT) protein. Work presented here demonstrated the presence of human SGT (hSGT) protein in a panel of human cell lines and throughout the cell cycle. To identify cellular processes in which hSGT is involved, knock down populations were analyzed which were generated through transfection of hsgt-specific small interfering RNA. Most strikingly, depletion of hSGT led to reduced proliferation of the affected cell populations while the mitotic index was increased. Time-lapse video microscopy revealed that cells from hSGT-depleted populations were unable to complete cell division due to mitotic arrest which was frequently followed by cell death. Further evidence for a role in cell division was given by the accumulation of hSGT in the midzone and the midbody, and by a mitosis-specific migration pattern of hSGT as detected by Western blotting after SDS-PAGE or two-dimensional gel electrophoresis. In conclusion, results obtained in this study demonstrate that hSGT protein is a constitutive component of all human cell lines tested and that this protein is essential for successful completion of cell division.
Available online 18 November 2003
Gesehen am 18.02.2021